Parental attitudes toward inclusion: Contributions of a quantitative study - Paulo C. Dias; Ana Rita Leal; Pedro Flores; Julian Diáz (Escola Superior de Educação de Paula Frassinetti, 2017)
Especially since the second half of the twentieth century, parents assumed a decisive position in civic and political movements in defense of inclusion, not always accompanied by sufficient research. The present study aims at understanding the attitudes of 177 parents of children with and without Special Educational Needs. According to the data, we mostly perceive favorable attitudes regarding the inclusion of children with SEN, although many individuals are undecided. We found differences between parents with and without children with SEN, especially among mothers, and a less favorable attitude among parents without children with SEN and with fewer children. The data present us clues about the current state and give us implications for real change at the school level. Keywords: Attitudes; parents; inclusion; school; survey.